2022
DOI: 10.3390/ijms232213806
|View full text |Cite
|
Sign up to set email alerts
|

A Proof-of-Concept Preclinical Study Using a Novel Thermal Insulation Device in a Porcine Kidney Auto-Transplantation Model

Abstract: Ischemia-reperfusion injury remains a fundamental problem during organ transplantation logistics. One key technical factor is the rapid allograft rewarming during the time of vascular reconstruction in the recipient. In this pilot study, a new thermal insulation bag (TIB) for organ transplantation was used. Insulation capacity, tissue compatibility, and usability were tested initially ex vivo on porcine kidneys (n = 24) followed by the first in vivo usage. Fourteen female German landrace pigs underwent kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Previous studies using TBB in a porcine kidney model showed that the core temperature of the kidney was lower than the surface temperature, suggesting that renal metabolic activity is suppressed by a sufficiently low surface temperature. 26 Here, we confirmed that TBB can maintain transplanted kidneys at a low temperature during vascular anastomosis and preserve the thermal threshold at the end of anastomosis.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies using TBB in a porcine kidney model showed that the core temperature of the kidney was lower than the surface temperature, suggesting that renal metabolic activity is suppressed by a sufficiently low surface temperature. 26 Here, we confirmed that TBB can maintain transplanted kidneys at a low temperature during vascular anastomosis and preserve the thermal threshold at the end of anastomosis.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, a recent report on a porcine kidney model demonstrated that TBB reduced tubular damage, indicated by decreased syndecan-1 expression compared with controls. 26 As the measurement of core temperature is not feasible in clinical studies, kidney temperatures were measured using a noncontact infrared thermometer. Previous studies using TBB in a porcine kidney model showed that the core temperature of the kidney was lower than the surface temperature, suggesting that renal metabolic activity is suppressed by a sufficiently low surface temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies using pig kidneys are important for demonstrating the efficacy of devices in humans, as these effects cannot be investigated in small animals. 15 Our research using pig kidneys investigates whether creating a hypobaric environment by placing the grafts in a sealed container during the initial perfusion can promote microthrombus removal and reduce graft damage during preservation and reperfusion.…”
mentioning
confidence: 99%
“…Their results show that, indeed, the two therapeutic strategies provide additive benefits to liver quality. Finally, Ernst et al [ 16 ] directed their efforts not towards preservation but instead towards alleviating the intermediate period between the end of preservation and anastomosis. Indeed, while the donor organ arteries and veins are anastomosed to the recipient circulation, the organ is subjected to the stress of warm ischemia, known to enhance IRI.…”
mentioning
confidence: 99%